2017
DOI: 10.1186/s12913-017-2681-6
|View full text |Cite
|
Sign up to set email alerts
|

Repeat testing for chlamydia trachomatis, a “safe approach” to unsafe sex? a qualitative exploration among youth in Stockholm

Abstract: Background Chlamydia trachomatis testing is offered to youth in Sweden, through a network of Youth Health Clinics, free at the point of care, in an attempt to bring down the prevalence and incidence of the infection. Nevertheless, infections rates have continued to rise during the past two decades and re-testing rates among youth for Chlamydia trachomatis has been reported to be high in Stockholm County. A few literature reports suggest that testing for sexually transmitted infections and the test result itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…HCPs viewed this as an opportunity to reach youth with primary prevention strategies. The notion that re-testing is as safe as using a condom was previously reported by our research team 22 and was confirmed by HCPs in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…HCPs viewed this as an opportunity to reach youth with primary prevention strategies. The notion that re-testing is as safe as using a condom was previously reported by our research team 22 and was confirmed by HCPs in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Findings in the present study were also triangulated with findings from a previous study. 22 Peer debriefing was conducted to validate our finding with other researchers.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Repeated testing after chlamydia infection due to unchanged risky behaviour has been discussed elsewhere [19,52,20,53]. It was recently reported that young adults who engage in unsafe sex possibly have repeated tests for chlamydia as a replacement for condom use [54]. The same study found that repeated testing gave a false sense of security when the chlamydia test was negative, while a positive chlamydia test resulted in repeated testing, but did not encourage changes in sexual behaviour [54].…”
Section: Discussionmentioning
confidence: 99%